Issues in the post-2005 TRIPS agenda - Benjamin Coriat; Luigi Orsenigo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2011)
Pharmaceuticals is one of the few industries in which patents are recognized as being key instruments for privately appropriating the economic benefits of innovation. Competition is largely based on innovation, and basic science is becoming increasingly crucial for the discovery and development of new products. Pharmaceuticals also occupy an extremely socially sensitive sector: large parts of the population increasingly perceive health care as a fundamental human right. For developing countries in particular, health has become a major issue, magnified by the tragedies of pandemics like HIV/AIDS. Controversies about the welfare implications of patents have characterized this industry ever since its inception. But in the last thirty years or so, the establishment of a strong tendency towards an extremely tight IP at the global level regime has made this debate even more heated. In this work, we begin by succinctly reviewing the main problems and the available evidence concerning the relationships between IPRs, innovation and welfare in pharmaceuticals. Next, we summarize the main theoretical arguments in favour and against (strong) IPRs in pharmaceuticals and present the little direct available empirical evidence, concerning respectively innovation and drug prices. Finally, we focus on TRIPS and Access to Care in developing countries, with particular reference to the case of HIV (the most emblematic example of the problems generated by enforcement of the TRIPS agreement).
Keywords: 330